The prognostic value of [18F]FDG PET/CT based response monitoring in metastatic melanoma patients undergoing immunotherapy: comparison of different metabolic criteria. - Sachpekidis, Christos; Weru, Vivienn; Kopp-Schneider, Annette; Hassel, Jessica C.; Dimitrakopoulou-Strauss, Antonia (European Journal of Nuclear Medicine & Molecular Imaging, 2023)
Purpose : To investigate the prognostic value of [18F]FDG PET/CT as part of response monitoring in metastatic melanoma patients treated with immune checkpoint inhibitors (ICIs). Methods: Sixty-seven patients underwent [18F]FDG PET/CT before start of treatment (baseline PET/CT), after two cycles (interim PET/CT) and after four cycles of ICIs administration (late PET/CT). Metabolic response evaluation was based on the conventional EORTC and PERCIST criteria, as well as the newly introduced, immunotherapy-modified PERCIMT, imPERCIST5 and iPERCIST criteria. Metabolic response to immunotherapy was classified according to four response groups (complete metabolic response [CMR], partial metabolic response [PMR], stable metabolic disease [SMD], progressive metabolic disease [PMD]), and further dichotomized by response rate (responders = [CMR] + [PMR] vs. non-responders = [PMD] + [SMD]), and disease control rate (disease control = [CMR] + [PMR] + [SMD] vs. [PMD]). The spleen-to-liver SUV ratios (SLRmean, SLRmax) and bone marrow-to-liver SUV ratios (BLRmean, BLRmax) were also calculated. The results of PET/CT were correlated with patients' overall survival (OS). Results: Median patient follow up [95% CI] was 61.5 months [45.3 – 66.7 months]. On interim PET/CT, the application of the novel PERCIMT demonstrated significantly longer survival for metabolic responders, while the rest criteria revealed no significant survival differences between the different response groups. Respectively on late PET/CT, both a trend for longer OS and significantly longer OS were observed in patients responding to ICIs with metabolic response and disease control after application of various criteria, both conventional and immunotherapy-modified. Moreover, patients with lower SLRmean values demonstrated significantly longer OS. Conclusion: In patients with metastatic melanoma PET/CT-based response assessment after four ICIs cycles is significantly associated with OS after application of different metabolic criteria. The prognostic performance of the modality is also high after the first two ICIs cycles, especially with employment of novel criteria. In addition, investigation of spleen glucose metabolism may provide further prognostic information.